2012
DOI: 10.3390/ijms13089992
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Mediated Gene Silencing Signals Are Not Graft Transmissible from the Rootstock to the Scion in Greenhouse-Grown Apple Plants Malus sp.

Abstract: RNA silencing describes the sequence specific degradation of RNA targets. Silencing is a non-cell autonomous event that is graft transmissible in different plant species. The present study is the first report on systemic acquired dsRNA-mediated gene silencing of transgenic and endogenous gene sequences in a woody plant like apple. Transgenic apple plants overexpressing a hairpin gene construct of the gusA reporter gene were produced. These plants were used as rootstocks and grafted with scions of the gusA over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 31 publications
2
25
1
Order By: Relevance
“…() and Flachowsky et al . (). However, both these studies were carried out on apple cultivars different from ‘Gala’ using different plasmids from those used in this work.…”
Section: Discussionmentioning
confidence: 97%
“…() and Flachowsky et al . (). However, both these studies were carried out on apple cultivars different from ‘Gala’ using different plasmids from those used in this work.…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that by RNA-mediated gene silencing signals are not graft transmissible from the rootstock to the scion in greenhouse-grown apple plants Malus sp. (Flachowsky et al, 2012). Further research is needed to reveal the molecular mechanisms and biological role(s) of the root-to-shoot (rootstockscion) transmission of RNA silencing.…”
Section: Root-to-shootmentioning
confidence: 99%
“…For example, the transfer of transgene-derived siRNAs from the transgenic cherry rootstocks to the non-transgenic scions in grafted trees was effective in inducing resistance to the Prunus necrotic ringspot virus [16]. In apples, however, the transmission of siRNAs from transgenic rootstock to non-transgenic scion was not observed [17]. Such contradictory data indicates that direct trials of rootstock-to-scion delivery are required to confirm the efficacy of the transgrafting technology for individual species.…”
Section: Introductionmentioning
confidence: 99%